Development of the Tool for Advancing Practice Performance, a practice-level survey to assess primary care structures and processes - Lorraine Kwok; Margaret M. Paul; Stephanie L. Albert; Daphna Harel; Saul B. Blecker; Bryan J. Weiner; Laura J. Damschroder; Deborah J. Cohen; Ann M. Nguyen; Donna R. Shelley; Carolyn A. Berry (PLoS ONE, 2025)
Despite progress to define primary care practice transformation models, there remain gaps in translating evidence-based guidelines into routine clinical care. Primary care providers (MD, DO, NP, PA) and researchers need tools to assess modifiable factors that improve practice performance to inform practice transformation efforts. We aimed to develop a pragmatic tool for assessing practice-level primary care structures and processes that are associated with better care quality and clinical outcomes. We generated 314 candidate items for the Tool for Advancing Practice Performance (TAPP) using data from a comprehensive literature review, Delphi study, and qualitative interviews with high-performing practices. We used empirical criteria and expert review to eliminate redundancy and improve clarity via removing and retaining items. The retained items were formatted into a survey tool, and we further revised the tool based on feedback elicited from cognitive interviews and pilot testing with primary care providers and staff. The final candidate pool comprised 126 items after refinement and expert review. For the survey tool, we adapted and developed survey questions for each of the 126 items. Eight cognitive interview participants reviewed the tool and provided feedback on its content and language. Based on this feedback, we eliminated 13 items because they were poorly or incorrectly understood by participants, resulting in a 113-item tool. Fifteen participants pilot tested the tool and no additional items were eliminated. The TAPP is a novel, low-burden tool that researchers and primary care providers can use to identify areas for improvement at the practice-level. Practices and health systems could use the TAPP to assess their own performance and identify gaps in their structures and processes, and practice networks and health systems can use the tool to assess structures and processes at individual clinics, track this information over time, and evaluate its relationship to care quality and clinical outcomes.